Characterization of seed-to-seedling transmission of Alternaria brassicicola in broccoli - Kaur, Navjot; Dutta, Bhabesh (Plant disease, 2024)
Alternaria brassicicola is a part of a complex of Alternaria species that causes leaf blight and head rot in brassica crops such as broccoli, kale, cabbage, cauliflower, and collards. Seed can serve as a potential source of inoculum for the transmission of A. brassicicola in broccoli as demonstrated earlier; however, seed-to-seedling transmission of pathogen was never characterized empirically. Hence, the objectives of this study were to (i) re-evaluate the effect of artificial seed infestation on seed germination and seed-to-seedling transmission of A. brassicicola in broccoli; (ii) determine the effect of A. brassicicola-seed inoculum levels on seed-to-seedling transmission; (iii) evaluate if variations in A. brassicicola -aggressiveness impact A. brassicicola seed-to-seedling transmission and, (iv) evaluate seed treatments that can reduce seed-to-seedling transmission of A. brassicicola in broccoli. Artificially infested seedlots were generated by inoculating broccoli seeds with a spore suspension of 1 × 105 conidia/ml of A. brassicicola using vacuum infiltration method. Inoculated (n=10 seedlots; 300 seeds/seedlot) or control seedlots in three replicates were planted on two layers of sterile blotter paper saturated with sterile water in transparent plastic boxes and incubated at 20°C and >90% RH under continuous fluorescent light. Percent seed germination and percent seed-to-seedling transmission were recorded every other day until 21 days. Percent seed germination was significantly affected with artificial pathogen inoculation. One hundred percent of the seedlots transmitted the pathogen to broccoli seedlings and seed-to-seedling percentages of the seedlots varied considerably. A strong linear and significant relationship between A. brassicicola inoculum level and seed-to-seedling transmission (%) within each seedlot was observed. Interestingly, variations in aggresiveness of A. brassicicola isolates did not affect seed-to-seedling transmission, as 100% of the seedlots were able to transmit the pathogen. Seed treatment with Miravis (a.i. pydiflumetofen 18.3%) significantly increased seed germination and reduced seed-to-seedling transmission percentages in A. brassicicola-inoculated seedlots. These results indicate that artificial seed inoculation with A. brassicicola can result in consistent seed-to-seedling transmission with significant impact on seed germination. Seed inoculum density of ≥104 conidia/ml is necesssary for reliable transmission of A. brassicicola. Further seed-to-sedling transmission is not dependent on aggresiveness of A. brassicicola isolates and, seed treatment with Miravis can significantly reduce pathogen transmission in broccoli seedings. Overall, this study provides detailed characterization of seed-to-seedling transmission of A. brassicicola in broccoli that can be further used to determine inoculum threshold, which has potential applications in seed-health testing and sample size determination. Further we also provide options for effective seed treatments that can significantly reduce A. brassicicola seed-to-seedling transmission and may potentially aid in managing seedborne fungal infection.